Cloning And Expression Of Alkaline Protease Gene From Bacillus Stearothermophilus Strain Fl - Ab.Hamid, Suhaili (2000)
Cloning of alkaline protease gene from a thermophilic bacteria, Bacillus stearothermophilus Fl (BSF1) was done by PCR cloning method. Genomic DNA of BSFI was extracted and the highest concentration obtained was 0.46 ug/uL and with a purity of 2.0. Three sets of primers were used including RM5 (5'-CA(CT) GG(ACGT) ACC AA(CT) GTG GC(CGT) GG-3) and RM6 (5'-(ACG)GG GGT (ACG)GC CAT GGA (CGT)CC-3', F0R900 (5-GCA TGC TAC GAT TAA ATA TC-3) and REV900 (5'-CGG CAA TAT CAC ITA GAG TAC C-3') and FOR900 (5'-GCA TGC TAC GAT TAA ATA TC-3') and REV1 591 (5-TGC AGC AGA AAG AAG GAA-3') which resuhed in amplification of 500-bp, 900-bp and 1 500- bp products, respectively. Southern blotting analysis suggested that both 500-bp and 900-bp fragment were present within the 1 500-bp fragment. E. coli TOPIOF